Tutorial: An Overview of UML 2.0 - Selic, Bran (International Conference on Software Engineering: Proceedings of the 26th International Conference on Software Engineering; 23-28 May 2004, 2004)
This half-day tutorial covers the salient aspects of the first major revision of the Unified Modeling Language UML 2.0. In this brief summary, we briefly review some of the main points covered in the tutorial.